К вопросу о моделировании воздействия ударной волны на корпус боевой машины - Бруль, С. Т.; Васильев, Антон Юрьевич (НТУ "ХПИ", 2005)
У статті пропонується методика автоматизованого аналізу впливу ударних хвиль різного походження на корпуси легкоброньованих машин. Описані можливі ушкодження об’єктів та обґрунтована необхідність аналізу подібних явищ. Наведено результати тестових скінченно-елементних розрахунків впливу ударної хвилі від потужного вибуху на корпус МТ-ЛБ.

In the article different origin shocks waves influencing on lightweight vehicles hulls automated analysis method is offered. Possible objects damages are described and similar phenomena analysis necessity is grounded. The results of test finite-elements computation of influencing of shock wave on the MT-LB hull are given
Keywords: военная техника; взрывные устройства; повреждения; прочностные характеристики; комплексная математическая модель; динамические расчеты; решение тестовых задач